ANALYSIS OF MULTIMODALITY ELEMENTS IN THE FILM "MY ANNOYING BROTHER" BY DINNA JASANTI USING A DIGITAL DISTRIBUTION APPROACH - Hasna Shofiyah; Wawan Hendrawan; Any Budiarti (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study examines the multimodality elements in the film My Annoying Brother by Dinna Jasanti using a digital distribution approach to understand how visual, auditory, and verbal elements interact to form narrative meaning. The purpose of this study is to identify the influence of digital distribution on the audience experience and how multimodal elements are delivered through digital platforms. Using a descriptive qualitative analysis method, data were collected through direct observation of the film and analysis of the elements that make up the film. The results show that the film utilizes visual elements such as image composition and color, auditory elements such as music and sound effects, and in-depth dialogue to develop characters and narratives. In addition, digital distribution through streaming platforms gives the audience greater control over the viewing experience, allowing them to engage more deeply with the film. This study provides new insights into the influence of digital distribution on how multimodal elements are received by the audience, as well as its contribution to the study of multimodality in film.